جوانب البناء القرآني للإنسان ودور العقيدة فيها: دراسة موضوعية عند سيد قطب من خلال تفسيره الظلال: The Qur’anic Aspects of Human Development With Special Reference to the Role of ‘Aqīdah in Tafsīr al-Zilāl of Sayyid Quṭb: A Thematic Study - Hocini, Mohamed Amine; Abdullah, Mustaffa; Bounama, Fouad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The study aims to clarify the Qur’anic aspects of human development and the role and effect of ‘aqīdah on it based on the thoughts of Sayyid Quṭb as in his tafsir of Fī Zilāl al-Qur’ān. The problem statement indicates the need to identify the types, priorities and mechanisms of human development according to the Qur’an as described in Fī Zilāl al-Qur’ān. It also aims to find out the position of ‘aqīdah in the development process as well as its relationship with other aspects. The study that used the method of thematic analysis shows the aspect of the Qur’an in human development as highlighted by Quṭb consists of four things namely, faith (‘aqīdah), spiritual, ethical and intellectual. However, Quṭb seems to neglect the discussion on physical aspect. He is found to emphasize the aspect of ‘aqīdah as the most important aspect and should be given priority, while other aspects are seen to firmly attached to it. These other aspects need to be consolidated and connected with each other. In addition, the study shows that each aspect needs to be developed through a specific mechanism such as various acts of worship like prayer, zakat and others.